Knowledge and perception on developmentally supportive care for preterm babies among staff nurses working in the neonatal intensive care unit of Tertiary Care Center in South India - Lavanya Subhashini; V Saritha; Monappa (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND AND AIM: As neonatal nurses play a significant job in providing care to preterm babies, awareness of developmentally supportive care would result in quality care of preterm infants and improved performance in nursing care. We aimed to assess the knowledge and perception of developmentally supportive care of preterm babies among staff nurses. MATERIALS AND METHODS: A cross-sectional study was conducted among 30 registered staff nurses. A purposive sampling technique was used to select the staff nurses with 1 year of working experience at the neonatal intensive care unit (NICU) of RL Jalappa Hospital and Research Center of Kolar, Karnataka. Self-administered questionnaire was designed to collect the data employing an online literature review for the purposes specified; data were analyzed using descriptive statistics. RESULTS: We analyzed the data and found that staff nurses are having adequate knowledge (70%) with mean scores of 20.9 ± 2.8, respectively, and positive perception toward the care of preterm babies in concern to developmentally supportive care. CONCLUSION: The study concludes that the knowledge and perception of NICU nurses regarding developmentally supportive care have found to be adequate. As developmentally supportive care would result in the improved performance and skill of the nursing personnel in providing care of preterm babies, higher authorities are advised to take it into account for the proper promotion of NICU staff nurses.